Synergy of cultural heritage, business, and technology as a path to success in museum management - A. I. Folkard (Путеводитель предпринимателя)
This article explores the synergy between cultural heritage, entrepreneurship, and technology through the lens of achieving success in museum management. In the modern era, this field is undergoing significant transformations under the influence of digital technologies, business strategies, and new formats for presenting cultural heritage. Against the backdrop of increasing commercialization, the challenge arises of finding and maintaining an optimal balance between preserving historical value, ensuring economic sustainability, and integrating technological innovations. On the one hand, an entrepreneurial approach and digitalization expand museum audiences and make exhibitions more accessible. On the other, there is a risk that educational and cultural missions may be compromised in favor of commercial interests.   The aim of this study is to analyze the aforementioned synergistic effect, including the impact of successful private initiatives, with a particular focus on the Sergey Dovlatov Apartment Museum.   The article examines key economic and technological trends and identifies contradictions in the academic literature related to the digitalization and commercialization of museum activities. The findings confirm that integrating cutting–edge technologies and business models into the museum sector not only enhances financial stability but also broadens the socio–cultural influence of museums, making them more accessible and interactive. The author emphasizes the need for interdisciplinary research that considers organizational, economic, technological, and cultural aspects. The materials presented in this study will be useful for professionals in the fields of museum management, cultural policy, entrepreneurship, and for researchers studying the impact of digital technologies on the preservation of cultural heritage.